PENGARUH MOTIVASI KERJA, KOMITMEN ORGANISASI DAN BUDAYA KERJA TERHADAP KINERJA GURU - Sri Asmawati; Sulistyo Sulistyo; Affan Afian (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, 2018)
The purpose of this study was to determine: (1) the effect of work motivation, organizational commitment and work culture on teacher performance in SMK Widya Dharma Turen, (2) the effect of work motivation on teacher performance in SMK Widya Dharma Turen, (3) the effect of organizational commitment on teacher performance at SMK Widya Dharma Turen, (4) the influence of work culture on teacher performance at SMK Widya Dharma Turen. This type of research uses explanatory research using multiple linear regression. This research was conducted at Widya Dharma Turen Vocational School with a total population of 36 teachers. Sampling was conducted with a saturated sample technique that is all teachers of Widya Dharma Turen Vocational School. Data collection uses questionnaires and documentation. The data obtained were analyzed with the help of SPSS application version 22.00 for windows. Based on the calculation results, it is known that: (1) there is an influence of work motivation, organizational commitment and work culture on teacher performance in SMK Widya Dharma Turen. (2) there is an influence of work motivation on teacher performance in SMK Widya Dharma turen. (3) there is an influence of organizational commitment to teacher performance in SMK Widya Dharma turen. (4) there is an influence of work culture on teacher performance in SMK Widya Dharma Turen.